Diaspora Organizations in International Affairs - Dijkzeul, Dennis; Fauser, Margit (Taylor & Francis, 2020)
Analyzing the role and impact of Diaspora Organizations (DOs) in International Relations (IR), this interdisciplinary volume provides empirical accounts of their work across Europe, the Americas, Africa and the Middle East. Over the last three decades, DOs have increased in number, spread to new regions, and addressed an ever-widening array of global problems, yet they have not received sufficient attention in IR in spite of the inter- and transnational nature of their involvements. Contributions explore important topics such as: The role of DOs in cooperation and conflict and in change and stability; DOs as transnational organizations and their degree of autonomy and power within the networks in which they operate; and The changing roles of DOs vis-à-vis states, regimes, and international organizations, when dealing with issues as diverse as peace, conflict, migration, integration, development, humanitarian action, human rights, religion, and economic growth. Demonstrating how IR can benefit from a stronger focus on DOs, this book will also help other disciplines gain insights into DOs and will prove useful to those in the fields of international relations, sociology, geography and anthropology.